REFORMULASI PENDIDIKAN MADRASAH ALIYAH MUHAMMADIYAH ENREKANG BERBASIS KEARIFAN LOKAL DALAM MENGHADAPI ARUS GLOBALISASI: TINJAUAN FILOSOFIS-PEDAGOGIS - Hamsina H; Hj.Fatimah Azis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
ABSTRACT This research examines efforts to renew the education system at Madrasah Aliyah Muhammadiyah Enrekang by adapting local wisdom values as a foundation in facing the dynamics of globalization. The main challenge identified is how to maintain the existence and contribution of Madrasah Aliyah Muhammadiyah Enrekang in the global educational environment without eliminating its inherent cultural characteristics. These issues encompass aspects of curriculum development, learning method innovation, educator capacity building, and provision of educational facilities that must be aligned with global standards while remaining grounded in local wisdom values. The methodology employed is a qualitative approach combining philosophical analysis and documentary review. Data collection was conducted through in-depth literature study from various sources, including educational policy documents, previous research studies, and theories about Islamic education, local wisdom, and globalization. The analysis was performed descriptively-interpretively, considering historical and socio-cultural aspects. The research reveals three significant findings: 1) Madrasah Aliyah Muhammadiyah Enrekang occupies a strategic position as an educational institution bridging traditional and modern values, 2) There are highly relevant local wisdom values to be integrated into the modern education system, such as mutual cooperation (gotong royong) and deliberation (musyawarah), 3) The developed integration model includes curriculum reformulation, contextual learning method development, and strengthening educator competencies in combining local and global values.